STRATEGI UNIT PELAKSANA TEKNIS DAERAH (UPTD) DALAM PENGELOLAAN MUSEUM SUBAK DI KABUPATEN TABANAN - PURNAMANINGSIH, PUTU EKA (Jurnal Ilmiah Widya Sosiopolitika, 2020)
UPTD Subak Museum was formedi with the aim ofapreserving traditionali farming tools usedi by ancient subak organizations. However, in its management there are stilli various problems, namely the low number ofavisits compared to other DTWs, overlapping authority, and limited use of DAK. In refining and / or making a strategy, it is necessary to analyze the strategy using strategic planning process indicators according to John M. Bryson and also SWOT analysis techniques according to Freddy Rangkuti to identify opportunities, threats, strengths, and weaknesses. The type of research used is descriptive qualitative. The informant determination technique used is purposive and snowball. The results of the SWOT matrix analysis yielded eight alternative strategies. The overall strategies described are four selected strategies as a priority scale for the UPTD Museum Subak, namely maximizing the use of technology as a means of disseminating information, fostering community business spirit to create a tourism industry around the Museum Subak area, developing museum marketing innovations to attract visitors, optimizing support from the central government. Keywords: UPTD Museum Subak, strategic planning process, SWOT analysis